Understanding Taxes, Complying with Obligations: A Literature Study on the Effect of Tax Understanding on Tax Compliance among MSME Taxpayers at the Jakarta Kalideres Tax Office - Arfikayani, Yuhanik; Firmansyah, Afandi; Putra, Yananto Mihadi (Social and Economic Bulletin, 2025)
This study aims to analyze the influence of tax understanding on the tax compliance of MSME taxpayers using a literature review and a case study at KPP Pratama Jakarta Kalideres. The literature review reveals that the level of tax understanding has a significant positive effect on MSMEs’ compliance in reporting and paying taxes. However, findings from the case study indicate that many MSME taxpayers still lack sufficient understanding of the procedures for reporting the Annual Tax Return (SPT) Form 1770 and have not adequately recorded their gross turnover. This condition reflects low tax literacy and understanding, which is a primary factor contributing to the low tax compliance among MSMEs in the area. The implications of poor tax understanding include increased risks of underpayment, administrative sanctions, and inaccurate reporting, all of which negatively impact state tax revenue. Conversely, improving tax understanding has the potential to enhance reporting accuracy, tax management efficiency, and higher compliance, thereby supporting the optimization of tax revenue for national development. Therefore, improving tax understanding among MSME actors is a key strategy to strengthen tax compliance and enhance the effectiveness of the national tax system.